Teledentistry: An Appraisal of Google Play Store Applications - Mujtaba, Hasan; Umer, Muhammad Farooq; Afroze, Eman; Chaudhary, Farooq Ahmad; Zofeen, Shumaila; Farid, Awais (European Journal of General Dentistry, 2023)
Objectives M-health technology facilitates and equips us with the required medical-related information and knowledge. This research work aims to provide an overview of m-health apps related to dentistry on the Google Play Store.Materials and Methods This widely used official smartphone platform was screened for the most widely available apps by putting the Medical Subject Headings (MeSH) and keywords “teledentistry, dentistry, and dental” and the resultant apps were evaluated for the number of downloads, ratings, release date, and number of reviews.Results The apps were categorized depending upon their applicability into different subgroups, which include patient education apps, dentist appointment apps, kid's apps, undergraduate apps, graduates and general dentist apps, postgraduate dentist apps, commercial and social networking apps, and other miscellaneous apps. The engagement of the users was evaluated in all the categories and the applicability of apps in respective categories was evaluated. The study concluded that despite plentiful apps in each category, the engagement of individuals with the m-health apps related to dentistry is relatively low. However, few creative apps in each category showed bright prospects for productivity and engagement.Conclusion Centralization and appropriately supervised apps with quality information by some official health care platforms can enhance the effectiveness and prepare this platform for the future of dentistry in the world of semantic web and blockchain.
Keywords: dental; dentistry; educational dentistry; online applications; android.